Using biodiversity to link agricultural productivity with environmental quality: Results from three field experiments in Iowa. Issue 2 (11th March 2013) - Liebman, Matt; Helmers, Matthew J.; Schulte, Lisa A.; Chase, Craig A.
Abstract: Agriculture in the US Corn Belt is under increasing pressure to produce greater quantities of food, feed and fuel, while better protecting environmental quality. Key environmental problems in this region include water contamination by nutrients and herbicides emitted from cropland, a lack of non-agricultural habitat to support diverse communities of native plants and animals, and a high level of dependence on petrochemical energy in the dominant cropping systems. In addition, projected changes in climate for this region, which include increases in the proportion of precipitation coming from extreme events could make soil and water conservation in existing cropping systems more difficult. To address these challenges we have conducted three cropping systems projects in central Iowa: the Marsden Farm Cropping Systems experiment, the Science-based Trials of Row-crops Integrated with Prairies (STRIPs) experiment, and the Comparison of Biofuel Systems (COBS) experiment. Results from these experiments indicate that (1) diversification of the dominant corn–soybean rotation with small grains and forage legumes can permit substantial reductions in agrichemical and fossil hydrocarbon use without compromising yields or profitability; (2) conversion of small amounts of cropland to prairie buffer strips can provide disproportionately large improvements in soil and water conservation, nutrient retention, and densities of native plants and birds; and (3) native perennial species can generate large amounts of biofuel feedstocks and offer environmental benefits relative to corn- and soybean-based systems, including greater carbon inputs to soil and large reductions in nitrogen emissions to drainage water. Increasing biodiversity through the strategic integration of perennial plant species can be a viable strategy for reducing reliance on purchased inputs and for increasing agroecosystem health and resilience in the US Corn Belt.